Structural adjustment in the OECS states and the role of the multilateral financial institutions - Ramchandran, N. (OECS CastriesLC, 1987)
Discusses the need for, effects of, and role of the private sector in structural adjustment focussing on the Nassau Understanding. Highlights the necessity for external financing and discusses the role of the World Bank in structural adjustment lending (SAL) to the OECS. Identifies the weaknesses of the OECS economies and outlines the components of SAL programs highlighting procedures for SAL and the details of financing such programs.